Group-based, person-centered diabetes self-management education: healthcare professionals’ implementation of new approaches - Stenov, Vibeke; Wind, Gitte; Vallis, Michael; Reventlow, Susanne; Hempler, Nana Folmann (BMC health services research, 2019)
Background Healthcare professionals’ person-centered communication skills are pivotal for delivering successful diabetes education. Many healthcare professionals favor person-centeredness as a concept, but implementation in practice remains challenging. Today, programs have often a fixed curriculum dominated by biomedical issues. Most person-centered methods are developed targeting individual consultations, although group-based programs are a widespread and efficient method of support. Person-centeredness in group-based programs requires a change in practice towards addressing biopsychosocial issues and facilitating group processes. The objective of this study was to explore how healthcare professionals implement new approaches to facilitate group-based, person-centered diabetes education targeting people with type 2 diabetes. Methods The study was guided by action research and divided into three studies: investigation, development, and pilot using a variety of qualitative methods. In the first study; observations across five settings were conducted. Forty-nine group participants and 13 professionals took part; the focus was to investigate approaches that supported or hindered person-centeredness in groups. Observations were supplemented by interviews ( n = 12) and two focus groups ( n = 16) with group participants, as well as interviews ( n = 5) with professionals. In the second study; 14 professionals collaborated in two workshops to develop new approaches. In the third study, new approaches were pilot-tested using observations in three settings. Twenty-five group participants and five professionals took part. The analysis of the pilot test led to the final workshop where six professionals took part. Results Implementation was characterized by three categories. Some professionals chose not to implement the methods because they conflicted with their practice relying on the biomedical model. Other incorporated some approaches but was unable to structure the process, leaving participants uncertain about the aim. Finally, one setting succeeded with implementation, tailoring content and processes to group participants’ needs. Conclusion The use of action research created context-sensitive approaches and increased professionals’ readiness to implement. More attention should be paid to systematic training of professionals. Training should be structured stepwise incorporating techniques directed towards existing skills including ample time to train and reiterate skills.